The effect of prehabilitation, targeting personalized biomechanical deficiencies, on female swim athletes´ functional capacity - Jauch, E.; Terry, K.; Hoogendyk, D.; Campbell, S. (International Journal of Exercise Science Conference Proceedings, 2025)
An athlete`s predisposition to injury is increased when their biomechanical function under sport specific, high load of tasks, is inefficient. Inefficient biomechanical function can be corrected by identifying and retraining neuromotor pathways via prehabilitation. Competitive swim athletes are at the highest risk of injury due to needing to overcome multiple interactive resistant forces under an extremely high training load. Swimmers are at a disadvantage due to limited technology available to identify biomechanical deficiencies.